Investigation of children's toys quality on the Macedonian market: determination of lead, cadmium and chromium levels - Mirvete Abdullahi1; Suzana Angelova; Evgenija Kiroska Petreska; Tatjana Kadifkova Panovska (Makedonsko Farmacevtski Bilten)
Information about heavy metal contamination in toys is essential to ensure the safety of the children’s product. However, 95% of the tested toys come from China, a country known for use of toy materials which are often banned in EU countries. In this paper the results from determination of three heavy metals levels (lead, cadmium and Trivalent chromium), in samples from children's toys available through specialized stores and markets in Republic of North Macedonia (RNM), are presented. The levels of lead, cadmium and Trivalent chromium in 28 samples, divided in three categories according to EN 71-3:2019, were determined using graphite furnace atomic absorption spectrometry (GF-AAS), after suitable sample preparation. The obtained results showed that the concentration of lead in the toys of the second category (purple slime and tattoo) are significantly higher than the maximum migrated limits (MML). Lead in children's toys originates from toxic lead dyes and can lead to serious health complications of central nervous system, cardiovascular, immune system and kidneys. Toys like finger paints had increased values of cadmium, but insignificantly higher compared to MML. Chromium concentrations did not exceed the MMLin all 28 toys. In summary, 14.3% of the tested toys had higher levels of the examined heavy metals than the regulatory limits. Therefore, improved quality control of children’s toys is an emerging issue to ensure consumers are purchasing safe, healthy and environmentally sustainable products.